The effect of benign and malicious envies on desire to buy luxury fashion items - Loureiro, S. M. C.; De Plaza, M. A. P.; Taghian, M. (Journal of Retailing and Consumer Services, 2019)
This study explores consumers’ desire for purchase of luxury fashion motivated by envy. Strong benign and malicious envies are psychological forces leading to action in various human endeavors including the purchase of products. Luxury fashion purchase and use in social settings motivated by envy is an attempt by some consumers to demonstrate social status and to claim success by targeting, matching, or exceeding the envied others. The conceptual models developed to guide this study enable comparing the influences of benign and malicious envies through the processes of admiration, affiliation and moral disengagement leading to the desire to purchase luxury fashion. Data collected from 202 shoppers in a mall intercept in Lisbon indicate that benign envy, as compared to malicious envy, is a stronger predictor of desire to purchase luxury fashion items and is a motivation to improve social image, project success and allow positive comparison with the desired social status. Theoretical and managerial implications are discussed.